A prospective study of PV cells and its effect on global warming, case study: North Cyprus - Azizian, M. Reza; Assefi, Hossein; Agboola, O. Phillips (World Scientific And Engineering Acad And Soc, 2008)
The concentration of CO2 in the atmosphere today is the greatest factor contributing to global warming. It is a known fact that fossil power plants are one of the major sources of CO2. These fossil power plants are mostly use in all nations as sources of electricity generation which the human race cannot detach from. Mostly in north Cyprus the air condition systems are used for both heating and cooling of domestic houses. Fossil fuels are being used to produce electricity in power plants leading to the generation of high amount of green house gases. In this study, as an alternative solution, using photovoltaic cells is considered to meet the electricity demand, and the feasibility analysis of photovoltaic cells for the consumers is shown. Moreover, the green house gases reduction, as a result of using photovoltaic cells, are evaluated.
4th IASME/WSEAS International Conference on Energy, Environment, Ecosystems and Sustainable Development -- JUN 11-13, 2008 -- Algarve, PORTUGAL
Keywords: photovoltaic cells; economic feasibility; energy efficiency; global warming; heating load; cooling load